2010
DOI: 10.1097/aud.0b013e3181c00eae
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Reflectance in Normal Caucasian and Chinese School-Aged Children and in Children with Otitis Media with Effusion

Abstract: A preliminary set of normative ER data have been generated for a pediatric population between the ages of 5 and 7 yrs, which were significantly different from previously gathered normative adult ER data. In this study, pediatric normative data were warranted for testing children, but ethnic-specific norms were not required to detect middle ear pathology and changes in middle ear status. WBR shows promise as a clinical diagnostic tool for measuring the mechanoacoustic properties of the middle ear and the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
117
5
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(156 citation statements)
references
References 56 publications
23
117
5
10
Order By: Relevance
“…The fastest decrease in CEOAE levels appear in children between birth and 2e4 years of age (Kon et al, 2000;Norton and Widen, 1990;Prieve et al, 1997). This progressive decrease can be partly explained by mechanoacoustical changes in the external and middle ear transmission characteristics, which change until at least 6 years of age (Beers et al, 2010;Hunter et al, 2008;Keefe and Levi, 1996). In this study, CEOAE levels in 5e10 year old children and adults were not significantly different.…”
Section: Ceoae Level Characteristicscontrasting
confidence: 65%
“…The fastest decrease in CEOAE levels appear in children between birth and 2e4 years of age (Kon et al, 2000;Norton and Widen, 1990;Prieve et al, 1997). This progressive decrease can be partly explained by mechanoacoustical changes in the external and middle ear transmission characteristics, which change until at least 6 years of age (Beers et al, 2010;Hunter et al, 2008;Keefe and Levi, 1996). In this study, CEOAE levels in 5e10 year old children and adults were not significantly different.…”
Section: Ceoae Level Characteristicscontrasting
confidence: 65%
“…These differences would affect the stiffness matrix in the FE model. Beers et al (2010) compared normal pediatric ER data (average age of 6.15 years) with normal adult ER data obtained by Shahnaz and Bork (2006). The results of Beers et al showed that ER was larger (corresponding to a smaller EA) in ears of Caucasian children than in adults at frequencies below 2 kHz.…”
Section: E Predicted Effects Of Mee On Ear-canal Middle Ear and Cocmentioning
confidence: 99%
“…These measures are used in research and clinical audiology with both adults and young children to differentiate between normal ears and ears with specific middle-ear disorders (Keefe et al, 1993;Feeney et al, 2003;Allen et al, 2005;Beers et al, 2010;Ellison et al, 2012;Hunter et al, 2013). EA is the fraction of incident energy absorbed by the ear at a probe inserted in a mid-canal location.…”
Section: Introductionmentioning
confidence: 99%
“…there is only one published study that analyzed wideband power reflectance in neonates with 27 to 78 hours of life (12) . Also, previous studies have shown a significant difference when comparing ethnic (13,14) and age groups (15) . Thus.…”
Section: Introductionmentioning
confidence: 99%